Credit-based Financing Instruments and the Development of Waqf Properties - Muhammad, Muhammad Tahir Sabit (CRES, FKSG, 2006)
The majority of the classic jurists disapproved loans and charges to be taken by the nazir or mutawalli of waqf. A handful of jurists in all four schools however did not agree if that was needed, necessary, and in the interest of waqf or :ines. Contemporary jurists follow the minority and have accepted the interest of waqf and its beneficiaries as i. foundation for the validity of transactions in waqf properties. While the old discussion was primarily based one. development financing as practiced by modern banks is not found in their discussions. Few contemporary e developed the old concepts based on the prevailing financial instruments (e.g. murabahah, istisna and ijarah), as recognized by Islamic financial institutions, in order to suite the nature of waqf. These instruments are modified in a manner that tries to develop the property while the ownership of the land remains with waqf institutions. Charges may be permitted but that would be subject to the life of the lease and license granted to the developing entity.